Analysis of Risk Factors Related to Malnutrition on Length of Stay Hospitalization: A Single-Center Observational Study at Klungkung General Hospital, Indonesia - Saskara, I Dewa Gde Wira; Christian (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Malnutrition is a prevalent issue in hospital settings, significantly impacting patient outcomes and healthcare costs. This study aimed to identify and analyze risk factors associated with malnutrition and its influence on the length of stay (LOS) among hospitalized patients at Klungkung General Hospital, Indonesia. Methods: A retrospective observational study was conducted, including adult patients admitted to Klungkung General Hospital between January 1, 2023, and December 31, 2023. Malnutrition was assessed using the Subjective Global Assessment (SGA) tool. Patient demographics, medical history, nutritional status, laboratory parameters, and LOS were collected. Univariate and multivariate analyses were performed to identify risk factors associated with malnutrition and its impact on LOS. Results: A total of 43,949 patients were included in the study, with 1,084 (2.46%) identified as malnutrition. The mean LOS for malnutrition patients was significantly longer than for well-nutrition patients (7.8 days vs. 4.2 days, p < 0.001). Multivariate analysis revealed that age ≥ 60 years (OR 2.31, 95% CI 1.85-2.89), presence of comorbidities (OR 1.75, 95% CI 1.42-2.16), low albumin levels (OR 2.05, 95% CI 1.68-2.50), and inadequate dietary intake (OR 1.98, 95% CI 1.61-2.43) were independent risk factors for malnutrition. Malnutrition was also an independent predictor of prolonged LOS (OR 1.68, 95% CI 1.36-2.07). Conclusion: Malnutrition is a significant problem at Klungkung General Hospital, associated with increased LOS. Early identification of risk factors and implementation of targeted nutritional interventions are crucial to improve patient outcomes and reduce healthcare costs.